Exergoeconomic analysis and optimization of a combined supercritical carbon dioxide recompression Brayton/organic flash cycle for nuclear power plants. (1st September 2018) - Wu, Chuang; Wang, Shun-sen; Li, Jun
Highlights: Supercritical carbon dioxide Brayton/organic flash cycle is proposed and analyzed. Exergoeconomic analysis and optimization are conducted. Supercritical carbon dioxide Brayton/organic flash cycle enhances the system performances. Several organic flash cycle working fluids are investigated. Abstract: A novel combined supercritical carbon dioxide recompression Brayton/organic flash cycle is investigated by means of exergoeconomic analysis. The supercritical carbon dioxide recompression Brayton/organic flash cycle is a combination of a supercritical carbon dioxide recompression Brayton cycle and an organic flash cycle where the organic flash cycle absorbs waste heat from the supercritical carbon dioxide recompression Brayton cycle for power generation. Seven different organic flash cycle working fluids are examined, including n -Nonane, n -Octane, n -Heptane, n -Hexane, n -Pentane, R365mfc and R245fa. Parametric study is employed to investigate the effects of the some decision variables on the first and second law efficiencies and the total product unit cost of the supercritical carbon dioxide recompression Brayton/organic flash cycle and the supercritical carbon dioxide recompression Brayton cycle. The performances of the supercritical carbon dioxide recompression Brayton/organic flash cycle and the supercritical carbon dioxide recompression Brayton cycle are optimized and then compared from the perspective of thermodynamics and exergoeconomics. The results show that the second law efficiency and the total product unit cost of the supercritical carbon dioxide recompression Brayton/organic flash cycle are up to 6.57% higher and up to 3.75% lower than those of the supercritical carbon dioxide recompression Brayton cycle, respectively. Compared with the supercritical carbon dioxide recompression Brayton/organic Rankine cycle, the supercritical carbon dioxide recompression Brayton/organic flash cycle can obtain slightly higher second law efficiency, and comparable or slightly lower total product unit cost. It can also be concluded that the highest second law efficiency and the lowest total product unit cost for the supercritical carbon dioxide recompression Brayton/organic flash cycle are achieved when the n -Nonane is used as the organic flash cycle working fluid.